Hackers rule. (Economist, 1999)
Comments on the quality of software which is developed by volunteers and given away. Computer software developers' protest against the payment of dues to Microsoft; Success of Linux as an example of software developed by a loose fraternity of volunteers rather than a firm's in-house programmers; Release of products from software firms such as Informix and Oracle which run on Linux; Advantages to the use of open-source software.